Design of Two-row Parallel Planetary Gear Mechanism based on Lever Method - Zhang Guofen; Liu Zhaojie; Liu Jinxia; Song Ruizhi (Jixie chuandong)
As the basic unit of complex transmission,two-row parallel planetary gear mechanism needs to be considered as whole in transmission ratio computation. According to the design requirements of vehicle automatic transmission,the design procedure for two-row parallel planetary gear mechanism is proposed based on the lever method using 3-node unified single-row single-stage and two-stage model,and the principle are illustrated by diagram. A new type of two-row parallel planetary gear mechanism（ single-stage and two-stage CC-SS） is designed and compared with the classical transmission A341 E（ single-stage and single-stage CR-SS）,4 T65 E（ single-stage and single-stage CR-RC）,AG4（ single-stage and single-stage CC-RR） and the transmission（ different case of single-stage and two-stage CC-SS） from a certain car,results show the new type of gear mechanism overall has obvious advantages of larger transmission ratio range,small transmission ratio step and least shifting components.